Numerical study on lubrication performance of engine main bearing with rough surface considering axial movement of crankshaft. (January 2020) - Li, Biao; Sun, Jun; Zhu, Shaoyu; Fu, Yangyang; Miao, Enming; Zhao, Xiaoyong; Wang, Hu; Teng, Qin; Ren, Yanping; Zhu, Guixiang
In actual operation of an engine, the crankshaft will move along the axis direction of engine main bearings under the combined influence of various influencing factors. Considering the axial movement and crankshaft deformation, a new lubrication model of engine main bearings with rough surface was built based on the average Reynolds equation. The influence of axial movement of deformed crankshaft on performance of main bearing with rough surface was studied. In this study, the axial movement law of deformed crankshaft is measured through experiment, and the finite element method was applied to solve the tilting of crankshaft in the bearing bore resulted from the crankshaft deformation. The results show that the axial movement of deformed crankshaft has a significant impact on performance of main bearing with rough surface. No matter whether or not the surface roughness is considered, the journal center trajectories of main bearings are unclosed three-dimensional space curve due to the axial movement of deformed crankshaft. The influence level of the axial movement of deformed crankshaft on lubrication characteristics of main bearings is directly related to the surface roughness. The influence trend and level of the surface roughness on lubrication characteristics of main bearings are obviously changed when considering the axial movement of crankshaft.